Acupotomy for third lumbar vertebrae transverse process syndrome: A protocol for systematic review. Issue 29 (17th July 2020) - Jiao, Lin; Xiao, Yuanyi; Chi, Zhenhai; Zhu, Daocheng; Ouyang, Xilin; Xu, Wei; You, Jianyu; Luo, Zhaona; Yuan, Fuqiang
Abstract: Background: Acupotomy has been widely used clinically to relieve low back pain. However, the efficacy of acupotomy for the third lumbar vertebrae transverse process syndrome is still uncertain. The aim of this study is to determine the effectiveness and safety of acupotomy therapy for the third lumbar vertebrae transverse process syndrome. Methods: Relevant randomized controlled trials will be searched from the databases of PubMed, the Cochrane Library, Embase, the China National Knowledge Infrastructure, Wanfang Database, Chinese Science and Technology Periodical Database, and Chinese Biomedical Literature Database from their inception to May 2020. Two reviewers will independently select studies, collect data, and assess the methodology quality by the Cochrane risk of bias tool. The RevMan V.5.3 will be used for meta-analysis. Results: This study will provide an assessment of the current state of acupotomy for the third lumbar vertebrae transverse process syndrome, aiming to show the efficacy and safety of acupotomy treatment. Conclusion: This study will provide evidence to judge whether acupotomy is an effective intervention for the third lumbar vertebrae transverse process syndrome. PROSPERO registration number: CRD42019134945.